Observer-Based Output Feedback Control with Linear Quadratic Performance - Kamarudin, Muhammad Nizam; Md Rozali, Sahazati; Husain, Abdul Rashid (Elsevier, 2013)
This paper discusses about the use of LQ performance optimality in the design of observer-based output feedback control for uncertain system with exogenous disturbance. The variable structure control law is adopted to compensate the uncertainty and disturbance. The separation principle is considered in the separate design of the feedback control law and observer. The design focuses on the SISO system and does not require the 'Kimura-Davison' conditions to be satisfied. An exploitation of LQR based method offers design freedom and less computational complexities and minimize the driving energy of the controller.